Size-Dependent Oxidation-Induced Phase Engineering for MOFs Derivatives Via Spatial Confinement Strategy Toward Enhanced Microwave Absorption - Xu, Hanxiao; Zhang, Guozheng; Wang, Yi; Ning, Mingqiang; Ouyang, Bo; Zhao, Yang; Huang, Ying; Liu, Panbo (Nano-Micro Letters, 2022)
Precisely reducing the size of metal-organic frameworks (MOFs) derivatives is an effective strategy to manipulate their phase engineering owing to size-dependent oxidation; however, the underlying relationship between the size of derivatives and phase engineering has not been clarified so far. Herein, a spatial confined growth strategy is proposed to encapsulate small-size MOFs derivatives into hollow carbon nanocages. It realizes that the hollow cavity shows a significant spatial confinement effect on the size of confined MOFs crystals and subsequently affects the dielectric polarization due to the phase hybridization with tunable coherent interfaces and heterojunctions owing to size-dependent oxidation motion, yielding to satisfied microwave attenuation with an optimal reflection loss of −50.6 dB and effective bandwidth of 6.6 GHz. Meanwhile, the effect of phase hybridization on dielectric polarization is deeply visualized, and the simulated calculation and electron holograms demonstrate that dielectric polarization is shown to be dominant dissipation mechanism in determining microwave absorption. This spatial confined growth strategy provides a versatile methodology for manipulating the size of MOFs derivatives and the understanding of size-dependent oxidation-induced phase hybridization offers a precise inspiration in optimizing dielectric polarization and microwave attenuation in theory. Highlights: 1 The size of metal organic frameworks (MOFs) derivatives was manipulated by a spatial confined growth strategy. 2 Dielectric polarization is the dominant dissipation mechanism due to the phase hybridization based on size dependent oxidation motion. 3 The specific reflection loss of synthesized Co/Co3O4 hollow carbon nanocages surpasses most reported MOFs derived counterparts for practical microwave absorption applications.